PENGARUH KEPEMIMPINAN KONTINJENSI DAN KEPEMIMPINAN SITUASIONAL TERHADAP KEPUASAN KERJA - Hardono Hardono (CV The Journal Publishing, 2020)
This study aims to examine whether situational leadership composed of contingency leadership and situational leadership affect employee job satisfaction in Panembahan Senopati Bantul organization and among the contingency leadership model variables and situational leadership models, which variable is most influential on employee job satisfaction in the Panembahan Senopati organization Bantul. The results of the t value for the contingency leadership model (X1) is greater than the value of t table (2.028) of 2.554 from the test shows that there is an influence of the contingency leadership model (X1) on job satisfaction (Y) of employees in the Panembahan Senopati Bantul organization, the model variable situational leadership (X2) obtained t count value is greater than the value of -t table (-2.028) of -1.334 and smaller than t table (2.028), the test shows that there is no influence of situational leadership model variables (X2) on satisfaction work (Y) employees in the Panembahan Senopati Bantul organization. From the F test results obtained F calculated values ​​greater than the F table value is 3.261> 3.259. That means, the contingency leadership model (X1) and situational leadership model (X2) simultaneously have influence on employee job satisfaction and from the t-test results it is known that the most influential factor is the cont leadership model concentration (X1) with a sig level of 0.015.